PELUANG PERDAMAIAN DALAM PKPU SOLUSI MENGHIDARI KEPAILITAN - Bahran, Khaerul (Ensiklopedia Education Review, 2025)
Abstract: This study aims to comprehensively analyze the factors influencing the success of peace plans in the Suspension of Debt Payment Obligations (PKPU) process in Indonesia, as well as to formulate an ideal guideline plan to achieve effective and sustainable peace efforts. Using a normative research method with a descriptive qualitative approach, secondary data were collected from relevant legislation, commercial court decisions, and pertinent legal and business literature. An in-depth analysis was conducted on Law Number 37 of 2004 concerning Bankruptcy and PKPU, focusing on the mechanisms of submission, approval, and ratification of peace plans.The research results identify that the success of peace plans is highly influenced by the synergy between the debtor's good faith in fulfilling obligations, majority creditor support for the proposed plan, the feasibility and suitability of the peace proposal with the debtor's actual condition, transparent and communicative management of the PKPU process, the active role of supervisory judges and commercial courts in overseeing and ratifying the peace plan, as well as compliance with legal provisions and timely submission.Keyword : PKPU, Peace Plan, Bankruptcy